Relationship between individual beliefs and usage of online knowledge sharing technology, and moderating effects of cognitive style among academicians in Malaysian Research Universities - Munusamy, Komathi (2016)
Knowledge is a crucial device for institutions of higher learning, more specifically to Research Universities. In fact, the growth of these institution ties solidly to their capability of obtaining, managing and sharing their knowledge. Knowledge sharing technologies i.e knowledge repositories are introduced and used in universities as an intellectual saviour in promoting the management and sharing of knowledge among the academic staffs. However, previous studies indicated that the knowledge that resides within individuals is hard to be transferred to others, as not all academics are willing to share it openly. Past literature has indicated a significant relationship between functional determinates and acceptance or rejection of a technology. However, most of the previous studies did not consider arousal as an emotional determinant in understanding the usage of online knowledge sharing technology. Thus, in this study, the technology acceptance model (TAM) and the hedonic consumption model was applied to examine the relationship between individual beliefs (perceived ease of use and perceived usefulness) and emotional element (arousal) towards usage of online knowledge sharing technology among academic staffs in research universities in Malaysia. Moreover, the study also examined the moderating effect of cognitive style on the relationship between the independent variables (perceived ease of use, perceived usefulness and arousal) and the dependent variable (usage of online knowledge sharing technology).In this quantitative study, a total of 321 respondents were surveyed. A multistage sampling technique was used to select the respondents from the five research universities in Malaysia. Data were gathered using a structured, self-administrated questionnaire where the items of the questionnaire were adopted from pervious literature. The questionnaires were administrated to the respondents by the researcher. The descriptive analysis were analysed using SPSS and the contribution of perceived ease of use, perceived usefulness and arousal on usage of online knowledge sharing technology were determined using structural equation modelling (SEM-AMOS). Results from the Pearson correlation analysis showed that, there is a significant relationship between perceived usefulness, perceived ease of use, arousal, and usage of knowledge sharing technology. Moreover, the analysis of the structural equation modelling indicated that the standardized path coefficient were consistent with the hypothesis by indicting the significant contribution of predictor variables to the outcome variables based on the goodness-of-fit indices: Chi – Square 2 (CMIN) = 489.913 (df = 203), Relative 2 (CMIN/df) = 2.413, p = .000, AGFI = .849, GFI = .879, CFI = .945, IFI = .945, NFI = .910, TLI = .937, RMSEA = .066. Moreover, the Structural Model also indicated that about 74% of variances in dependent variables i.e. usage of online knowledge sharing technology was explained by the predictor variables entered into the Structural Equation Modeling respectively. Base on the standardized regression weight in the hypothesized path model showed that perceives ease of use, perceived usefulness and arousal are significant predictors of usage of online knowledge sharing technology. Moreover, the relationship between arousal and usage of online knowledge sharing technology was further strengthen with cognitive style.as a moderator. The findings of this study can be used by policy makes to implement policies and activities to strengthen the emotional bonding between academics and the technology in order to facilitate knowledge sharing behaviour in research universities in Malaysia.